KEEFEKTIFAN METODE TIME TOKEN DALAM PEMBELAJARAN MENGANALISIS ISI TEKS EKSPOSISI PADA PESERTA DIDIK KELAS X SMA NEGERI 3 PEMALANG TAHUN PELAJARAN 2019/2020 - Wahyu Bambang Pratama; Asrofah Asrofah; Zainal Arifin (Philosophica: Jurnal Bahasa, Sastra, dan Budaya, 2019)
This research is motivated by the lack of interest of students to be active in receivinglearning to analyze the contents of the exposition text. Motivation and creativity areneeded to present learning that fosters students' interest in learning and receiving material.The method chosen based on the innovation of the researcher presents an interesting andimpartial method of active and less active students with the time token method. Relatedto the background of the problem, the main problem studied is how is the effectivenessof the time token method in learning to analyze the contents of exposition text in classX students of SMA Negeri 3 Pemalang in the academic year 2019/2020? The purpose ofthis study is to describe the effectiveness of the time token method in learning to analyzethe contents of exposition text in class X students of SMA Negeri 3 Pemalang in theacademic year 2019/2020. The research method used in this study is quantitative. Theresearch data were obtained from the results of tests and non-tests of class X studentsof SMA Negeri 3 Pemalang in the academic year 2019/2020. In quantitative research thedata obtained from the test results will be analyzed with the data analysis techniques ofnormality test, homogeneity test and t-test. Based on the results of the study obtained anaverage value of 81.286 experimental class with a good value category. While the controlclass obtained an average value of 59.071 with a less value category. This proves that thetime token method is effective in learning to analyze the contents of exposition text inclass X students of SMA Negeri 3 Pemalang in the academic year 2019/2020.